The Dead Sea Scrolls in Ancient Media Culture - Keith, Chris; Stuckenbruck, Loren T.; Williams, Travis B. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
Media studies is an emerging discipline that is quickly making an impact within the wider field of biblical scholarship. This volume is designed to evaluate the status quaestionis of the Dead Sea Scrolls as products of an ancient media culture, with leading scholars in the Dead Sea Scrolls and related disciplines reviewing how scholarship has addressed issues of ancient media in the past, assessing the use of media criticism in current research, and outlining potential directions for future discussions.